Instantaneous Formation of Silk Protein Aerosols and Fibers with a Portable Spray Device under Ambient Conditions. Issue 7 (27th January 2023) - Choi, Jaewon; Sahoo, Jugal Kishore; Hasturk, Onur; Falcucci, Thomas; Yao, Ya; Kaplan, David L.
Abstract: A variety of artificial silk spinning approaches are attempted to mimic the natural spinning process found in silkworms and spiders, yet instantaneous silk fiber formation with hierarchical structure under physiological and ambient conditions without post‐treatment procedures remains unaddressed. Here, this work reports a new strategy to fabricate silk protein‐based aerosols and silk fibers instantaneously in situ using a spray device, avoiding complicated and costly advanced manufacturing techniques. The key to success is the instantaneous conformational transition of silk fibroin from random coil to β‐sheet right before spraying by mixing silk and polyethylene glycol (PEG) solutions in the spray device, allowing aerosols and silk fibers to be sprayed, with further control achieved via the molecular weight of silk. The spinning process of the spray device is based on the use of green solvents, that is, all steps of instant conformational transition of silk fibroin are carried out in aqueous conditions or with buffers at ambient conditions, in combination with shear and elongational flow caused by the hydraulic pressure generated in the spray container. The system supports a portable and user‐friendly system that could be used for drug delivery carriers, wound coating materials, and rapid silk fiber conformal coatings on surfaces. Abstract : This work provides strategies to fabricate silk protein‐based materials ranging from interconnected fiber structures to aerosols in situ using a simple spray device under physiological and ambient conditions, where the instantaneous conformational transition of silk fibroin to β‐sheets occurs right before spraying through the mixing of silk and polyethylene glycol solutions in the spray device.